CONSTRUCTION OF SYAIKH AHMAD MUHAMMAD SYĀKIR'S METHOD IN REVIEWING THE BOOK OF SUNAN TIRMIDZI - Sholihin, Sholihin (Nabawi: Journal of Hadith Studies, 2023)
Shaykh Ahmad Muhammad Shākir is one of the scholars who gave advice on the book Sunan Tirmidhi. Among the many styles of sharia methods from several scholars, Muhammad Shākir has his own characteristics and patterns. The description of this method has not been found in journal articles in Indonesia. Therefore, the researcher reviews the sharaḥ method used by Shaykh Muhammad Shākir in his recitation of Sunan Tirmidhi's book and its implementation in other sharaḥ books, as well as the composition of the sharaḥ method. Through qualitative methods, this research concludes that Shaykh Muhammad Shākir's method in teaching Sunan Tirmidhi's book is theijmāli method. The reason for this method is closely related to the four patterns that Shaykh Muhammad Shākir has in the following hadith lectures: (1) sharaḥ hadith with hadith, (2) the words of ṣahābat, (3) kalam tabi‘in, (4) using ijtihad and style of language. In his lecture, Shaykh Muhammad Shākir uses several compositions such as mentioning the full name of the author of the hadith, nahwu, fiqh issues, and a description of the lafadz hadith. [Syaikh Ahmad Muhammad Syākir merupakan salah satu ulama yang mensyarahi kitab sunan tirmīżī. Di antara banyak corak metode syarah dari beberapa ulama, Muhammad Syākir memiliki ciri khas dan pola tersendiri. Penjabaran metode ini belum ditemukan di artikel jurnal di Indonesia. Oleh karenanya, peneliti mengulas metode syarah yang digunakan Syaikh Muhammad Syākir dalam mensyarah kitab Sunan Tirmīżī dan implementasinya dalam kitab syarah lain, serta komposisi metode syarahnya. Melalui metode kualitatif, penelitian ini menyimpulkan bahwa metode Syaikh Muhammad Syākir dalam mensyarah kitab Sunan Tirmīżī adalah metode ijmāli. Alasannya metode tersebut erat kaitannya dengan empat pola yang dimiliki Syaikh Muhammad Syākir dalam mensyarah hadis berikut ini: (1) syarah hadis dengan hadis, (2) perkataan sahabat, (3) kalam tabi‘in, (4) menggunakan ijtihad dan gaya bahasa. Dalam pensyarahannya, Syaikh Muhammad Syākir menggunakan beberapa komposisi, seperti menyebutkan nama lengkap dari perawi hadis, nahwu, masalah fikih, dan uraian lafaz hadis.]